The Restrictive Interpretation of Article 9 of the Constitution of Japan and the Right of Self-Defense - Mosciatti Gómez, Giancarlo (Revista Tribuna Internacional, 2023)
The principle of renunciation of war established in Article 9 of the Japanese Constitution has historically been interpreted strictly. The present work carries out a brief historical analysis about the consequences and effects derived from that, to later study certain proposals and documents of the Executive that tried an interpretative flexibility, until the discussions on the concepts of "enemy base" and "functions of command and control” that are currently being debated in Japan, from a perspective of International Law and, especially, of the right of self-defense established in the Charter of the United Nations.